Swedish Sign Language Corpus, version 1 - Mesch, Johanna; Wallin, Lars; Nilsson, Anna-Lena; Bergman, Brita (Stockholm University, 2020)
The Swedish Sign Language Corpus includes recordings and documentation of sign language texts, produced by Swedish Sign Language signers.

The corpus material is freely available via the web-based corpus tool STS corpus, for use in teaching, research, and sign language lexicography. By logging in, additional material and files are available.

Svensk teckenspråkskorpus omfattar inspelade videomaterial och dokumentation av teckenspråkstexter, producerade av teckenspråkiga.

Korpusmaterialet är fritt tillgängligt via det webbaserade korpusverktyget STS-korpus, detta för användning inom undervisning, forskning och teckenspråkslexikografi. Genom inloggning finns tillgång till ytterligare material och filer.
Svensk teckenspråkskorpus, version 1
Keywords: Sign Language; Teckenspråk; MEDIA, COMMUNICATION AND LANGUAGE; MEDIA, KOMMUNIKATION OCH SPRÅK; Humanities and the Arts; Humaniora och konst; Languages and Literature; Språk och litteratur